Analisis I-Girder Baja Pada Jembatan Lengkung Horizontal Menggunakan Standar AASHTO LRFD 2012 - MT, Mukhlis; Hamid, Desmon; Murdiansyah, Lukman; Army, B; Mucni, Rifki (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2019)
Horizontal curved bridge is a bridge with a cross section of a curved steel I-girder that requires complex geometry and has certain requirements. which different between a straight bridge with a horizontal curved bridge that is in addition to the vertical bending effect and the shear effect is also influenced by torsional effects, lack of stability, and special constructive attention, and consideration of system behavior in the analysis. The purpose of writing this final project is to be able to do the bridge structure modeling using Midas Civil software, to design the structure of the horizontally curved steel I-girder bridge, and Obtaining the dimensions of I-Girder steel horizontally curved bridge that is able to resistance the effects of curvature and loads that work in accordance with predetermined conditions, and know the behavior of elements from horizontally curved steel I-Girder bridge. This design refers to AASHTO LRFD 2012 and design carried out namely three continuous span (42 m + 55 m + 42 m) by using two pieres. the dimensions of steel I-girder with 2000 mm girder height of 20 mm body thickness, top flange width 500 mm thickness 25 mm, and bottom flange width 600 mm thickness 40 mm. From the results of the girder design there are some of conditions which can be said to be extreme because comparison between the compressive stress with capacity almost the same, that is 99.8% at the inertia-x on maximum positive moment fatigue condition, 95% at the inertia-y on maximum positive moment strength lime state condition, and 98% the maximum positive moment Constructibility on torsion. This proves that every agreed has extreme. However, this value is still within safe limits in accordance with the standards used.